Monitoring the effect of urban development on urban heat island based on remote sensing and geo-spatial approach in Kolkata and adjacent areas, India. (November 2021) - Halder, Bijay; Bandyopadhyay, Jatisankar; Banik, Papiya
Highlights: The temperature has been increased 4.72 °C in last thirty years over the study area. The built-up land was increased 33.758% over Kolkata and adjacent area. The vegetation area has been decreased 25.521% due to urban expansion. The UHI increased central, north and southern parts of this study area. The UTFVI maps were indicated that the ecological condition dynamics. Abstract: Climate change and the rapid urbanization process can trigger the current urban heat island effect. An urban heat island is categorized by temperature variation between urban and rural environments. Urban areas are mostly hotter than rural areas due to urbanization, population pressure, industrialization, vegetation insufficiency, and transportation system. Thermal remote sensing was used to carry out the exploration of urban heat islands over Kolkata municipality and surrounding urban and rural-urban fringe areas, India. This study was identify the land use/land cover change dynamics and land surface temperature analysis as well as the correlation analysis of LST, LULC, NDVI, and NDBI. Built-up areas were located 22.01% (1990), 31.44% (2000), 44.21% (2010) and 55.768% (2020). The Annual temperature was increased 0.157 °C per year. The relationship between LST and NDVI was showing a negative correlation because of the vegetated area affected due to urban expansion. The relation between LST and NDBI resulted in a positive correlation because of anthropogenic activities. The CA-ANN was used for LULC prediction of the year 2030 and 2050 for future urban expansion and environmental degradation. Those areas need proper planning for better healthy livelihood and also protect our environment otherwise climate change will affect the entire location.